Comparative study of the performance of buffalo calves and cow calves by feeding Urea Molasses Block with straw based diet - Ferdousi, S; Masum, AKM; Khan, MAS; Islam, MA (Journal of the Bangladesh Agricultural University, 2010)
An experiment was conducted to evaluate the performance of buffalo calves and cow calves supplementing Urea Molasses Block (UMB) with straw based diet. Three cow calves (average 1 year & 8 months age and 111 kg body weight) and three buffalo calves (average 1 year & 10 months age and 89 kg body weight) were grouped into A and B, respectively and fed for 60 days. It was found that, the DMI (kg/h/d) was 5.66±1.18 and 6.10±0.99, respectively in group A and B (p>0.05). The DMI in 1st and 2nd fortnight of the experiment in group A and B were 5.77±0.31 and 6.17±0.33; 4.96±0.43 and 5.77±0.39, respectively (p<0.01). But, the DMI in 3rd and 4th fortnight differs nonsignificantly (p>0.05). At the end of the experiment, the final body weight for group A and group B were 132.6±11.96 and 113±8.19 kg, respectively (p>0.05). The body weight gain per day for both groups were 0.36±0.05 and 0.40±0.05 kg, respectively (p>0.05). The average heart girth gain per day in group A and group B were 0.24±0.02 and 0.30±0.03 cm, respectively (p>0.05). The average wither height gain per day was 0.075±0.005 and 0.059±0.005 cm in group A and B, respectively (p<0.05). The average body length gain per day for group A and group B were 0.31±0.03 and 0.36±0.04 cm, respectively (p>0.05). The growth performance of buffalo calves is better than cow calves by feeding UMB with straw based diet. Keywords: UMB; Body weight; Heart girth; Wither height; Body length DOI: 10.3329/jbau.v8i1.6404 J. Bangladesh Agril. Univ. 8(1): 87-90, 2010